Quaternary landscape evolution of patagonia at the Chilean Triple Junction: Climate and tectonic forcings. (1st June 2021) - Tobal, Jonathan E.; Morabito, Ezequiel García; Terrizzano, Carla M.; Zech, Roland; Colavitto, Bruno; Struck, Julian; Christl, Marcus; Ghiglione, Matías C.
Abstract: Glacial and fluvial landforms record the recent history of the Earth surface and have the potential to provide information about uplift and climate changes during Quaternary times. Patagonia hosts uniquely well-preserved moraine deposits, along with outwash and fluvial terraces. This offers the possibility of determining the timing of glacier advances since the Great Patagonian Glaciation (ca. 1.2 Ma) and allows us to investigate landscape response to climate and tectonic forcing. In this study, we present twenty-eight new in situ 10 Be exposure ages for glacial deposits, outwash sediments, and fluvial terraces at the latitude of the Chile Triple Junction (∼46°30′S). We combine this database with a detailed mapping and a morphological analysis of the Deseado River terrace system. The glacial and outwash deposits document at least five major glacial advances in the Lago Buenos Aires valley before the deposition of the Moreno system during Marine Isotope Stage (MIS) 8. Key advances occurred during MIS 12 and MIS 16. Further ice expansions that resulted in Telken V and VI/VII outwash surfaces date to 780 ka and ca. 1.2 Ma respectively. Overall, our data show the difficulty of dating pre-LGM glacial deposits using surface exposure methods and reinforce the idea that outwash surfaces are better targets to determine the age of glacial sequences in the region. The Deseado River terrace system yields stratigraphically consistent ages that range from 1167 to 447 ka, which indicate that these terraces formed during Pleistocene times. Our analysis suggests that terraces T3, T7 and T8 may have been formed during cold stages, close to the glacial-interglacial transitions. We also calculated incision rates that reveal a strong initial pulse, from ca. 1200 to 900 ka, which was followed by significantly weaker river incision pulses. Finally, our geomorphological analysis confirms that the oldest fluvial terraces of the Deseado River system exhibit a NE-SW tilting through a broad area, next to the Atlantic Ocean. This was previously interpreted as the surface response to a long-wavelength dynamic uplift, a phenomenon that should be reassigned to the early Pleistocene. Highlights: Surface exposure ages from fluvial terraces in Patagonia were obtained for the first time. 10 Be ages obtained from four levels of the Deseado River Terrace indicate that they were formed during Pleistocene times. Fluvial incision rates show an initial, ∼200 ka long, phase of strong incision, followed by a significant decreasing trend. Ages obtained from glacial deposits highlight the significant challenges of exposure dating of old moraines. The geomorphological analysis confirms a regional tilt affecting previously recognized by Guillaume et al. (2009).